GENE ACTION OF SOME AGRONOMIC TRAITS IN MAIZE BY HALF DIALLEL CROSS AT TWO LOCATIONS IN SULAIMANI -IRAQ - F. M, Lawand; I. Towfiq, S.; Abdulkhaleq, D. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This research was aimed to study combining ability for growth, kernel yield, and its components, for maze (Zea mays L.) inbred lines, which evaluated in 8×8 diallel crosses. At two locations, Dukan and Qlyasan, at the Sulaimani region. Significant genetic variability was found in all genotypes for all characters except no. of ears/plant. Highest significant general and specific combining ability were observed for most characters, revealing the importance of both additive and non-additive gene action, at the same time a low ratio of Ϭ2GCA/ Ϭ2SCA was recorded for all traits at both locations vice versa the average degree of dominance was more than one, this indicates to the high contribution of a non-additive gene effect. Heritability in broad sense was found to be high, while a narrow sense, it was low for all traits at both locations. Significant differences were noticed between both locations for kernel yield and most of its components, confirming the exceeding Dukan location.